Cooperatives as the Strengthening Effort for Oil Palm Replanting Program in Landak Regency - Afifah, Husnun Puspa; Nurliza, Nurliza; Kurniati, Dewi (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 1 (2021): Vol.15, No.1, 2021DO - 10.24843/SOCA.2021.v15.i01.p03, 2021)
Palm oil is one of the important plantation commodities in Indonesia's economic activities. Palm oil plants require rejuvenation (replanting) due to the decreasing productivity that caused by the old age of the plants (more than 25 years). Replanting is an effort to replace old oil palm plantations to maximize the income. The function and role of the cooperative is needed to be involved in the management of oil palm replanting. Cooperatives are a common need for farmers to manage their plantations, especially those related to management, plants, and financial techniques. The objective of this research was to optimize the role of cooperatives in an effort to strengthen the oil palm replanting program in Landak Regency. 22 respondents were taken by purposive sampling. This research used descriptive analysis. Data analysis used was Rap-Rep palm oil (Rapid Appraisal Replanting of palm oil) from the modification of Rapfish with Microsoft Excel software. The results of the research show that the replanting technical dimension, human resource development, and supporting elements are not optimal. Sensitive attributes that influenced the cooperative optimization in oil palm replanting program in Landak Regency are (1) Funding; (2) Institutions (3) Land Requirements ; (4) Training in Financial Management and Administration (5) Post Harvest Processing Tools; (6) Pesticides and Alsintan.